FORMATION OF SOFTWARE DESIGN SKILLS AMONG SOFTWARE ENGINEERING STUDENTS - Striuk Андрій (Journal of Information Technologies in Education (ITE), 2022)
The paper is devoted to the one of the competence components of a mobile-oriented environment for software engineering (SE) students. It is shown that the introduction of the higher education standard for SE bachelors has created a number of problems to ensure the quality of training, primarily related to low level of specification both for competencies and learning outcomes. The way to solve these problems is to design a detailed system of professional competencies for SE bachelors. The paper considers approaches to the formation of the important special professional competency of future software engineers – K14 (ability to participate in software design, including modeling (formal description) of its structure, behavior and functioning processes). Based on a historical and genetic review of the software design training among SE students in the UK, USA, Canada, Australia, New Zealand and Singapore, recommendations for choosing of software design teaching techniques, selection of learning content, modeling and design tools, assessment of the level of formation of the relevant competence are developed. The example of the industrial-like software design training (studio training) is considered. The problems of transition from architectural to detailed design and project implementation are shown. Prospects for further development of this study are to substantiate the third (after requirements engineering and design engineering) engineering component of SE – software constructing.